2020
DOI: 10.1126/sciadv.aaw8938
|View full text |Cite
|
Sign up to set email alerts
|

Revealing roles of competing local structural orderings in crystallization of polymorphic systems

Abstract: Most systems have more than two stable crystalline states in the phase diagram, which is known as polymorphism. Crystallization in such a system is often under strong influence of competing orderings linked to those crystals. However, how such competition affects crystal nucleation and ordering toward the final crystalline state is largely unknown. This is primarily because the competition takes place locally and thus is masked by large positional fluctuations. We develop a unique method to correctly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 64 publications
1
20
0
Order By: Relevance
“…Such crystal nucleation behavior was directly confirmed by confocal microscopy experiments in colloidal systems by Tan et al [118]. We have found that preordering also plays a critical role in the polymorph selection by simulations [116] and confocal microscopy experiments [119]. Furthermore, we have confirmed that this scenario of crystal nucleation is valid for soft spheres [120] and water [121], indicating the universality of this scenario of crystal nucleation [117].…”
Section: Crystallizationsupporting
confidence: 77%
“…Such crystal nucleation behavior was directly confirmed by confocal microscopy experiments in colloidal systems by Tan et al [118]. We have found that preordering also plays a critical role in the polymorph selection by simulations [116] and confocal microscopy experiments [119]. Furthermore, we have confirmed that this scenario of crystal nucleation is valid for soft spheres [120] and water [121], indicating the universality of this scenario of crystal nucleation [117].…”
Section: Crystallizationsupporting
confidence: 77%
“…We use two structural order parameters, which are coarsegrained bond orientational order parameters, W 6 and Q 6 , to quantify the single-particle-level local structures (see Methods on their definitions). W 6 is used to distinguish fcc and bcc by its sign (W 6 ≥ 0 for bcc and W 6 < 0 for fcc), whereas Q 6 quantifies the degree of crystalline order of the solid (particles with Q 6 < 0.35) are regarded as defective structures, which mainly consist of highly distorted (defective) solids with a small amount of liquidlike (Q 6 < 0.25) particles 21,22,[39][40][41] (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…W 6 is used to distinguish fcc and bcc by its sign ( W 6 ≥ 0 for bcc and W 6 < 0 for fcc), whereas Q 6 quantifies the degree of crystalline order of the solid (particles with Q 6 < 0.35 are regarded as defective structures, which mainly consist of highly distorted (defective) solid and a amall amount of liquid-like ( Q 6 < 0.25) particles.) 21 , 22 , 39 41 (Fig. 2 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several scenarios such as a classical one-step crystallization process, a nonclassical two-step crystallization mechanism with precursors consisting of local regions with either high density, high bond-orientational order, or competing orders, or a spinodal-like process have been proposed, but all of these crystallization mechanisms are still heavily debated. 1 10 …”
Section: Introductionmentioning
confidence: 99%